Method of intermediate problems in the Fröhlich polaron model - Soldatov, A.V. (Condensed Matter Physics, 2009)
Method of intermediate problems in the theory of linear semi-bounded self-adjoint operators on rigged Hilbert
space was applied to the investigation of the ground state energy of the Frohlich polaron model. It was shown
that various infinite sequences of non-decreasing improvable lower bound estimates for the polaron ground
state energy can be derived for arbitrary values of the electron-phonon interaction constant. The proposed
approach allows for explicit numerical evaluation of the thus obtained lower bound estimates at all orders
and can be straightforwardly generalized for investigation of the low-lying branch of the slow-moving polaron
excitation energy spectral curve adjacent to the ground state energy of the polaron at rest. In conjunction
with numerous, already derived by multitudinous methods, well-known upper bound estimates for the energy
spectral curve of the Frohlich polaron as a function of the electron-phonon interaction constant and the polaron
total momentum, the aforesaid improvable lower bound estimates might provide one with virtually precise
magnitude for the energy of the slow-moving polaron. Метод промiжних задач в теорiї лiнiйних напiвобмежених самоспряжених операторiв у пристосованому просторi Гiльберта використовується для дослiдження енергiї основного стану в моделi полярона Фрьолiха. Показано, що для довiльних значень константи електрон-фононної взаємодiї можуть бути отриманi рiзнi безмежнi неспаднi послiдовностi оцiнок знизу для енергiї основного стану полярона. Запропонований пiдхiд дозволяє отримати точнi числовi оцiнки знизу у всiх порядках i може бути узагальнений для вивчення нижньої гiлки енергетичного спектру збуджених станiв повiльного полярона, що межує з енергiєю основного стану нерухомого полярона. В комбiнацiї з iншими добре вiдомими пiдходами до оцiнки зверху залежностей енергетичного спектру полярона Фрьолiха вiд константи електрон-фононної взаємодiї i повного iмпульсу полярона вищезгаданi оцiнки з уточненням знизу можуть забезпечити знаходження практично точних значень для енергiї полярона, що повiльно рухається.